2022
DOI: 10.3390/cancers15010098
|View full text |Cite
|
Sign up to set email alerts
|

Hotspot on 18F-FET PET/CT to Predict Aggressive Tumor Areas for Radiotherapy Dose Escalation Guiding in High-Grade Glioma

Abstract: The standard therapy strategy for high-grade glioma (HGG) is based on the maximal surgery followed by radio-chemotherapy (RT-CT) with insufficient control of the disease. Recurrences are mainly localized in the radiation field, suggesting an interest in radiotherapy dose escalation to better control the disease locally. We aimed to identify a similarity between the areas of high uptake on O-(2-[18F]-fluoroethyl)-L-tyrosine (FET) positron emission tomography/computed tomography (PET) before RT-CT, the residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Using prospectively acquired data on 30 patients, Dissaux et al demonstrated the greater reproducibility of morphological MRI sequences and 18F-FET PET/CT over functional MRI sequences [15]. However, the possible impact of delineation variability on survival endpoints was not analyzed [15][16][17][18]. Using volumes defined by spectroscopy or morphological MRI sequences or even PET/CT, several teams have studied the impact of dose escalation.…”
Section: Introductionmentioning
confidence: 99%
“…Using prospectively acquired data on 30 patients, Dissaux et al demonstrated the greater reproducibility of morphological MRI sequences and 18F-FET PET/CT over functional MRI sequences [15]. However, the possible impact of delineation variability on survival endpoints was not analyzed [15][16][17][18]. Using volumes defined by spectroscopy or morphological MRI sequences or even PET/CT, several teams have studied the impact of dose escalation.…”
Section: Introductionmentioning
confidence: 99%